Shortened Tracer Uptake Time in GA-68-DOTATOC-PET of Meningiomas Does Not Impair Diagnostic Accuracy and PET Volume Definition - Josefine Graef (Diagnostics, 2020)
Ga-68-DOTATOC-PET/MRI can affect the planning target volume (PTV) definition of meningiomas before radiosurgery. A shorter tracer uptake time before image acquisition could allow the examination of more patients. The aim of this study was to investigate if shortening uptake time is possible without compromising diagnostic accuracy and PET volume. Fifteen patients (f = 12; mean age 52 years (34–80 years)) with meningiomas were prospectively examined with dynamic [68Ga]Ga-68-labeled [DOTA0-Phe1-Tyr3] octreotide (Ga-68-DOTATOC)-PET/MRI over 70 min before radiosurgery planning. Meningiomas were delineated manually in the PET dataset. PET volumes at each time point were compared to the reference standard 60 min post tracer injection (p.i.) using the Friedman test followed by a Wilcoxon signed-rank test and Bonferroni correction. In all patients, the earliest time point with 100% lesion detection compared to 60 min p.i. was identified. PET volumes did not change significantly from 15 min p.i. (p = 1.0) compared to 60 min p.i. The earliest time point with 100% lesion detection in all patients was 10 min p.i. In patients with meningiomas undergoing Ga-68-DOTATOC-PET, the tracer uptake time can safely be reduced to 15 min p.i. with comparable PET volume and 100% lesion detection compared to 60 min p.i.